Uso de las Técnicas de Modulación Codificada para el Incremento de la Capacidad de Sistemas de TV Digital por Satélite - Matos Gómez, Jorge (Ingeniería, 2001)
This paper shown the comparative analysis between the use of TCM-8PSK instead of QPSK and a variable code-rate convolutional inner code that is used in DVB-S standard. It is shown that the use of the former technique allows for a higher capacity in terms of number of programs (or digital contents) without modify the transmission bandwidth and MPEG-2's source coding. It is also analyzed the impact on the terminal ground receiver.